Tauhid and Taqwa: The Soul in the COSO-ERM Framework -An Imaginary Research Dialogue- - Mohamad Djasuli (Master of Accounting Universitas Trunojoyo Madura, 2020)
This research is an imaginary dialogue between two internal auditors of a state university. They are called as a religious senior auditor and a junior auditor. The imaginary dialogue used spirituality in order to avoid misunderstanding and heartache of each other. Both of them discuss current issues in regard to internal control as a soul and foundation to achieve the organization's objectives. This research is to discuss the concept of internal control built by the Committee of Sponsoring Organizations of the Treadway Commission (COSO), whether is it enough to be the guardian system or is there missing elements that should be discovered? They will use the COSO-ERM (Entreprises Risk Management) as the modification of COSO, as the internal control world considers risk management is the key to prevent an organization from failure nowadays. Finally, this research offer a deconstruction of the COSO-ERM framework to become The Tauhid Taqwa-COSO-ERM Framework with Tauhid and Taqwa as the most foundation of all things in the framework especially for the human as the operator in all level.Keywords: tauhid, taqwa, COSO-ERM, and internal control